Coronary Calcium Score for the Prediction of Asymptomatic Coronary Artery Disease in Patients With Ischemic Stroke - Choi, Hye-Yeon; Shin, Soo Jeong; Yoo, Joonsang; Lee, Kijeong; Song, Dongbeom; Kim, Young Dae; Nam, Hyo Suk; Lee, Kyung Yul; Lee, Hye Sun; Kim, Dong Joon; Heo, Ji Hoe (Frontiers in Neurology, 2020)
Purpose: Many patients with ischemic stroke have concomitant coronary artery disease (CAD). However, it remains unclear which stroke patients should undergo evaluation for asymptomatic CAD, and which screening tools are appropriate. We investigated the role of coronary artery calcium (CAC) score as a screening tool for asymptomatic but severe CAD in acute stroke patients. We determined the selection criteria for CAC screening based on risk factors and cerebral atherosclerosis. Materials and Methods: The present study included consecutive patients with acute stroke who had undergone cerebral angiography and multi-detector computed tomography coronary angiography. Severe CAD was defined as left main artery disease or three-vessel disease. Enrolled patients were randomly assigned to two sets; a set for developing selection criteria and a set for validation. To develop selection criteria, we identified associated factors with severe CAD regarding clinical factors and cerebral atherosclerosis. CAD predictability of selection criteria with the CAC score was calculated. Results: Overall, 2,658 patients were included. Severe CAD was present in 360 patients (13.5%). CAC score was associated with CAD severity (P<0.001). In the development set (N=1860), severe CAD was associated with age >65 years (odds ratio [95% confidence interval], 2.62 [1.93–3.55]), male sex (1.81 [1.33–2.46]), dyslipidemia (1.77 [1.25–2.61]), peripheral artery disease (2.64 [1.37–5.06]) and stenosis in the cervicocephalic branches, including the internal carotid (2.79 [2.06-3.78]) and vertebrobasilar arteries (2.08 [1.57-2.76]). We determined the combination of clinical and arterial factors as the selection criteria for CAC evaluation. The cut-off criterion was two or more elements of the selection criteria. The area under the curve (AUC) of the selection criteria was 0.701. The AUC significantly improved to 0.836 when the CAC score was added (P<0.001). In the validation set (N=798), the AUC of the selection criteria only was 0.661, and that of the CAC score was 0.833. The AUC of the selection criteria + CAC score significantly improved to 0.861(P<0.001). Conclusion: The necessity for CAC evaluation could be determined based on the presence of risk factors and significant stenosis of the cervicocephalic arteries. CAC evaluation may be useful for screening for severe CAD in stroke patients.